Impact of Perceived Convenience, Satisfaction, and Tax Understanding on E-Filing Adoption Intention: The Moderating Role of IT Benefits - Ardhiatul Halima Tuasalamony; Muh. Ainul Yaqin; Sitti Rahma Sudirman; Nur Alfiah Rezkiyanti (Universitas Muhammadiyah Makassar, 2025)
This study investigates the influence of perceived convenience, perceived satisfaction, and tax understanding on the intention to adopt e-Filing among individual taxpayers registered at KPP Pratama Tenggarong. In addition, this research examines the moderating role of perceived information technology benefits in strengthening these relationships. Using a quantitative approach, primary data were collected from 100 respondents through offline and online questionnaires distributed to individual taxpayers who submitted their annual tax returns via e-Filing. The sampling technique used was purposive sampling, and data were analyzed using SmartPLS version 4.1 with measurements based on a five-point Likert scale. The findings reveal that perceived convenience, perceived satisfaction, and tax understanding each have a significant positive effect on taxpayers’ intention to use e-Filing. These results indicate that when taxpayers perceive e-Filing as easy to use, satisfactory, and supported by adequate knowledge of taxation procedures, their willingness to adopt the system increases. However, the study also finds that perceived benefits of information technology do not moderate the relationship between perceived convenience, perceived satisfaction, and tax understanding on e-Filing adoption intention. This suggests that although taxpayers recognize the advantages of technology, such perceptions do not necessarily strengthen their intention to use e-Filing. The study contributes to the enrichment of Technology Acceptance Model (TAM) development by incorporating satisfaction, tax understanding, and IT benefits as extended variables. Practically, the results provide insights for tax authorities to improve e-Filing services by enhancing system usability, ensuring user satisfaction, and increasing taxpayers’ understanding to support higher adoption rates.